If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 1 = 3 Reorder the terms: 1 + Y = 3 Solving 1 + Y = 3 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + Y = 3 + -1 Combine like terms: 1 + -1 = 0 0 + Y = 3 + -1 Y = 3 + -1 Combine like terms: 3 + -1 = 2 Y = 2 Simplifying Y = 2
| -7/10*1/2 | | 6(3x+2)=6(8x+2)+4 | | -7/10x1/2 | | 2r+20=2000 | | 5y+4=3x | | 7+13r-3=9r+81-7r | | (x+1)+(x+5)+5=180 | | 5+15=x | | 21/8=x/1680 | | y=90(300)+1000 | | -4x+(-2x+5)=-2x | | y=90(28000)+1000 | | x/-5=-5-(-8) | | y=90(200)+1000 | | 6(2-x)/5=-x | | x^2-6x+66=0 | | y=90(200)+200 | | y=90(100)+1000 | | 15x-20=100 | | 0.2(x+80)+0.2x=20 | | d^2-16d+63=0 | | 15x-20=140 | | y=1/5(-15)+6 | | y=1/5(0)+6 | | 8=-4y | | 30+30j= | | x=-4(2) | | x=-4(0) | | 11x+6=13x-6 | | x+4(4)=12 | | z^2-11z-30=0 | | y=1/2(-6) |